2014
DOI: 10.1186/s12879-014-0690-1
|View full text |Cite
|
Sign up to set email alerts
|

Using internet search queries for infectious disease surveillance: screening diseases for suitability

Abstract: Background: Internet-based surveillance systems provide a novel approach to monitoring infectious diseases. Surveillance systems built on internet data are economically, logistically and epidemiologically appealing and have shown significant promise. The potential for these systems has increased with increased internet availability and shifts in health-related information seeking behaviour. This approach to monitoring infectious diseases has, however, only been applied to single or small groups of select disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
74
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 35 publications
3
74
0
Order By: Relevance
“…This study aimed to investigate the capacity of internet-based approaches to help monitoring a wide range of seasonal and non-seasonal infectious diseases in Australia. The results were consistent with our previous study that assessed the level of correlation between monthly search metrics and disease notification14. Based on the Spearman correlation results, eight diseases exhibited high degree of correlation with the investigated search metrics and were identified as having promise for nowcasting.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study aimed to investigate the capacity of internet-based approaches to help monitoring a wide range of seasonal and non-seasonal infectious diseases in Australia. The results were consistent with our previous study that assessed the level of correlation between monthly search metrics and disease notification14. Based on the Spearman correlation results, eight diseases exhibited high degree of correlation with the investigated search metrics and were identified as having promise for nowcasting.…”
Section: Discussionsupporting
confidence: 90%
“…Data sources used for this may include online news stories or case reports, as is used by HealthMap7 (http://healthmap.org/); Wikipedia access logs8; social media (such as Twitter)91011; or may use participatory approaches (crowdsourcing) for data collection12. The majority of work has, however, focused on the use of Internet search metrics6131415. Approaches based on internet search metrics hypothesize that, when people contract a disease, they will search for information on their condition/symptoms on the internet and that accurate estimates of disease occurrence in the community may be produced by monitoring changes in the frequency of specific searches.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the use of Web-based data heavily relies on crowdsourcing from the public and their engagement online. Similarly, other applications such as digital disease detection and surveillance work on a similar basis to effectively utilize the continuous generation of Web-based data from this growing digital age [3,4]. However, in this study, the applications of infoveillance in health research are specifically evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…There is strong evidence regarding the predictive utility of search activity and infectious disease outbreak from digital epidemiologic studies. Milinovich et al [4] identified 17 infectious diseases that were positively correlated with search activity trends on Google, with a majority being vaccine-preventable, vector-borne, and sexually transmitted diseases. Most recently, the Colombian Zika virus outbreak showed positive association with search activities made on Google [5].…”
Section: Introductionmentioning
confidence: 99%